Fecundity of the crab Callinectes ornatus Ordway, 1863 (Decapoda, Brachyura, Portunidae) from the Ubatuba region, São Paulo, Brazil - Mantelatto, FLM; Fransozo, A. (E J Brill, 1997)
The objective of the present study was to characterize the fecundity of Callinectes ornatus from the northern coast of São Paulo, Brazil. To study the fecundity and its relationships to size, brood weight, and egg size, the ovigerous females were collected at 2-month intervals for two consecutive years (January, 1991 to November, 1992) in the Ubatuba region using a fishing boat equipped with an otter-trawl type of net. After collecting, the animals were screened, bagged, labeled, and stored frozen. Only data from 38 females carrying early stage eggs were considered. In the laboratory, the specimens were thawed at room temperature, the pleopod structure with the egg mass was removed and the eggs were carefully removed from the pleopods. The samples were then fixed in 10% formalin and stored in 70% ethanol, until the time for processing. Processing followed the method of Hines (1982, 1988). Following the frequency determination of carapace width and fecundity, mean egg number, mean volume and mean dry weight of brooded egg mass were determined for each class obtained. Data were analyzed by regressions of log-log transformations for allometric plots (Y = aX(b)) of reproductive variables versus carapace width. Carapace width was one of the main factors for the determination of fecundity, which ranged 171 570 +/- 94 634 eggs, with females of the same size class presenting a wide amplitude of variation. This supports the hypothesis that portunid females present staggered spawning, possibly presenting more than one period of reproduction within one year. The present species showed lower fecundity than the remaining portunids studied, but they did show a rapid and efficient embryonic development, presumably capable of assuring reproductive success.